The Concept and Essence of Administrative and Legal Protection of Tax Relations - K. S. Rohozinnikova (Law and Safety)
The concept and essence of administrative and legal protection of tax relations have been considered. It has been emphasized that the study of general theoretical ideas about the correlation between the concepts of legal security and legal protection will contribute to solving the tasks of the research. The provisions on the correlation of legal security and legal protection in the whole and as a part have been supported. The author has established peculiarities of administrative and legal protection compared with other types of legal protection of public relations: such activity is carried out by public administration agencies through administrative and legal means, including coercive ones. The essential components of administrative and legal protection, which should form the basis of its definition, include: prevention of negative phenomena; detection of possible violations; overcoming harmful consequences (restoration of violated rights); maintaining stable legal relations; prosecuting persons who encroach on the protected object.